The profile of patients presenting with postpartum depression seen in the Department of Obstetrics and Gynaecology at Dr George Mukhari Academic Hospital - Bernadette M. Muluvhu; Solomon Rataemane (South African Journal of Psychiatry, 2018)
Introduction: Postpartum depression is one of the most common psychiatric complications of childbearing women. Most studies report that it has a high prevalence, but women at risk are rarely recognised during pregnancy and post-delivery. It is therefore often missed and, as a result, it has negative effects not only on the mother but also on the newborn infant.